(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
The sorption of Cu(II) from aqueous solutions by peat containing sorbent was studied in a dynamic mode. Peat sample was taken from Lake Sevan (near Vardenis in Gegharkunik region of Armenia). The data obtained from sorption experiments were analyzed using Langmuir and Freundlich models. Langmuir equation describes sorption isotherm of Cu(II) with high correlation coefficients, better than Freundlich model. According to Langmuir model, the maximum uptake capacity of peat containing adsorbent for Cu(II) was obtained as about 15 mg/g. The sorption properties of peat were estimated by ICP-MS.